Mechanical Behavior and Calculation Method for RC Fifteen-Pile Cap of Mixed Passenger and Freight Railway Bridge - Hongmeng Huang; Lu Cui; Wei Lu (Advances in Civil Engineering)
The thickness, reinforcement, and concrete strength grade of railway caps in China are generally determined according to the force, yet the method for calculating the force is unclear. To date, there is no desirable calculation method for analyzing the caps. Based on the fifteen-pile thick cap of mixed passenger and freight railway, the influencing factors on cap bearing capacity were analyzed using finite element method (FEM). The variations of load-bearing capacity and mechanical behavior of thick cap were characterized by introducing rigid angle α. Results indicated that ultimate load-bearing value of the cap increased linearly with the increase of concrete strength grade, and an increasing load-bearing capacity of the reinforcement distributed in the pile diameter range was larger than that of the uniform reinforcement; when the reinforcement ratio was 0.15%, it increased by 9.3%. The cap showed punching failure when α < 45°. The reaction force at each pile top under vertical load was not equal; thereby, the cap was not absolutely rigid. The principal compressive stress trajectories in the concrete were distributed in the range of connecting the pile and the outer edge of the pier, and the effective tensile stresses in the reinforcement were mainly distributed in the diameter range of pile and pile connection, which is in accord with the stress mode of the ordinary spatial truss model. Based on this, a spatial truss model applicable to the design of railway caps is proposed, and a method for calculating reaction force at pile top and formulas for calculating the bearing capacity of strut and tie were presented. The feasibility of the proposed method was also verified by comparison with FEM results.